Mapping forest landscape patterns - Remmel, Tarmo K.; Perera, Ajith H. (Springer Nature, 2017)
"This book explores the concepts, premises, advancements, and challenges in quantifying natural forest landscape patterns through mapping techniques. After several decades of development and use, these tools can now be examined for their foundations, intentions, scope, advancements, and limitations. When applied to natural forest landscapes, mapping techniques must address concepts such as stochasticity, heterogeneity, scale dependence, non-Euclidean geometry, continuity, non-linearity, and parsimony, as well as be explicit about the intended degree of abstraction and assumptions. These studies focus on quantifying natural (i.e., non-human engineered) forest landscape patterns, because those patterns are not planned, are relatively complex, and pose the greatest challenges in cartography, and landscape representation for further interpretation and analysis."--Resumé vydavatel
Keywords: mapování; lesy; dálkový průzkum Země; krajinná ekologie; mapping; forests; remote sensing; landscape ecology; elektronické knihy; sborníky; electronic books; papers of several authors